Preventive and therapeutic effects of JM-20 on paclitaxel-evoked painful peripheral neuropathy in rats - Bárbara B. Garrido-Suárez; Gabino Garrido; Addis Bellma Menéndez; Guillermo Aparicio; Odalys Valdés; Estael Ochoa-Rodríguez; Yamila Verdecia-Reyes; René Delgado-Hernández (GarVal Editorial Ltda., 2021)
Context: JM-20 is a hybrid synthetic molecule, which is based on a multimodal drug design paradigm for cerebrovascular disease. In addition to its neuroprotective effects, JM-20 also decreased sciatic nerve chronic constriction injury (CCI)-induced mechanical hypersensitivity in rats. JM-20 has a strong mitoprotective ability, and its effects could be in correspondence with the mitotoxicity hypothesis for paclitaxel-induced painful peripheral neuropathy. Aims: To evaluate the efficacy of the JM-20 to reduce neuropathic pain manifestations induced by the administration of paclitaxel in rats. Methods: In this study was implemented a rat model of painful peripheral neuropathy, produced by the chemotherapeutic agent paclitaxel, to determine whether JM-20 (10 mg/kg, p.o) could prevent the development of neuropathic pain during the exposure to paclitaxel. As well as to determine whether JM-20 (20 mg/kg, p.o) could reverse the established neuropathic pain. Mechanical behavioral assessment using von Frey filaments applied to the hind paws was applied before, during, and after treatments for 35 days. Results: Giving JM-20 during the exposure to paclitaxel significantly reduced the severity of mechanical allodynia and mechanical hyperalgesia. Moreover, JM-20 significantly reduced both established neuropathic pain manifestations. There was no evidence of tolerance to the effect during three days of dosing, and a long-term effect was observed after JM-20 discontinuation. Conclusions: JM-20 may be clinically relevant for both the prevention and treatment of paclitaxel-induced painful peripheral neuropathy.